PERHITUNGAN HARGA OPSI EROPA MENGGUNAKAN MODEL BINOMIAL MULTIPERIODA (STUDI KASUS SAHAM TELKOM.JK) - noor Sofiyati (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2020)
Binomial Model is one of method to determine the option price. In this model, assumed that the stock price only move up or down in the each steps. In this journal will be reviewed the risk neutral world assumption and real world to determine option price and knowing how to calculate option payoff for european option from stock price use Binomial Multiperoid Model with different strike price.